The CA125 regression rate to predict overall survival differ between paclitaxel-containing regimen and nonpaclitaxel regimen in patients with advanced ovarian cancer. Issue 5 (1st August 2002) - Tsuda, H.; Hashiguchi, Y.; Nakata, S.; Deguchi, M.; Negoro, S.; Ishiko, O.; Yamamoto, K.
Abstract : In this study, we compare the time to normalization of CA125 after cytoreductive surgery between a paclitaxel-containing regimen and a non-paclitaxel regimen. This study demonstrates that CA125 regression in a paclitaxel-containing regimen was slower than that in a non-paclitaxel regimen. When we determine the CA125 regression rate to predict overall survival in ovarian cancer, we should take into account the kind of chemotherapy regimen, especially the use of paclitaxel.